PENGARUH KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN WELLNESS MEDICAL CENTER DI KOTA JAKARTA TIMUR - Anastalia, Anastalia; Edy Krisyanto (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the effect of Organizational Commitment and Organizational Culture on Employee Turnover Intention at Wellness Medical Center in East Jakarta. The research method used is a quantitative method with an associative approach. Data collection was conducted by distributing questionnaires to the entire population of 62 using a saturated sampling technique, resulting in a sample of 62 respondents. The data analysis techniques used in this study included validity testing, reliability testing, normality testing, classical assumption testing, linear regression analysis, correlation coefficient testing, coefficient of determination, and hypothesis testing. The results of this study indicate that Organizational Commitment (X1) has a negative and significant effect on employee Turnover Intention partially, as shown by the calculated t-value < -t table (-4.144 < -2,000), a significance value of 0.000 < 0.05, and a regression equation of Y = 48.937 – 0.502X1, as well as a correlation value of -0.472 and a coefficient of determination value of 22.2%. Organizational Culture (X2) has a negative and significant effect on employee Turnover Intention partially as shown by the t-value < -t table (-4.262 < -2,000), a significance value of 0.000 < 0.05, and a regression equation of Y = 53.577 – 0.582X2, as well as a correlation value of -0.482 and a coefficient of determination of 23.2%. Organizational Commitment (X1) and Organizational Culture (X2) simultaneously have a significant effect on Employee Turnover Intention, as indicated by the f count value > f table (11.327 > 3.150), a significance value of 0.000 < 0.05, and the regression equation Y = 56.257 – 0.294X1 – 0.368X2, as well as a correlation value of 0.527 and a coefficient of determination value of 27.7%. Keywords: Organizational Commitment, Organizational Culture, Turnover Intention